'Gonna make yer gorgeous': Everyday transformation, resistance and belonging in the care-based hair salon. (May 2016) - Ward, Richard; Campbell, Sarah; Keady, John
This paper makes a contribution to an emerging debate on dementia and citizenship through a focus on the everyday experiences of women living with dementia and in receipt of care. In particular, a link is drawn between hairdressing and citizenship in the context of dementia care. Informed by a wider debate over the importance of an emplaced, embodied and performative approach to citizenship, the authors highlight the way that intersecting forms of resistance unfold in the salon. The Hair and Care project, as the name implies, focused upon hair care and styling in the context of a wider consideration of appearance and how it is managed and what it means for people living with dementia. With a focus upon the routine, mundane and thereby often unproblematised aspects of everyday life in/with care, the discussion draws together two key ideas concerned with the interplay of power and resistance: Essed's (1991) theory of 'everyday discrimination' and Scott's (1985) notion of 'everyday resistance'. The findings illuminate the creative and collective forms of agency exercised by older women living with dementia, in the context of their relationships with one another and with the hairdressers whose services and support inspire their loyalty and patronage. Findings from the study point to the link between (inter-)personal practices of appearance management and a wider set of social conditions that are manifest in the on-going struggle over time, space and bodies in dementia care.